PUBLIC OPINION ON THE EFFECTIVENESS OF “OBIDIENTS” USE OF SOCIAL MEDIA IN THE CAMPAIGN FOR PETER OBI IN 2023 ELECTIONEERING - Jibrin Umar Omachi; Ogunyemi E. Oluwafisayo; Daniel T. Ezegwu (International Studies Journal)
This study examined public opinion on the effectiveness of “Obidients” use of social media in the campaign for Peter Obi in 2023 electioneering. The objectives of the study were to assess the extent to which the "Obidients" campaigned for Peter Obi in the 2023 Nigerian presidential election; find out the social media platforms through which Obidients campaigned for Peter Obi in the 2023 presidential election and evaluate the effectiveness of "Obidients" social media campaigns in mobilizing support for Peter Obi in the 2023 Nigerian presidential election. The Uses and Gratification theory served as the theoretical framework. Survey was the research design while questionnaire was the research instrument. The findings of the study showed that the "Obidients" effectively utilized social media to promote Peter Obi's candidacy and interact with potential voters. Also, the "Obidients" employed various social media platforms to campaign for Peter Obi, with Whatsapp being the most frequently utilized channel. Based on the findings, the researcher recommended that political actors should recognize the importance of social media in political campaigning and develop strategies to effectively leverage its power. It was also recommended that the preferences and habits of the target audience should be carefully considered when developing media campaigns, with a particular focus on messaging apps such as Whatsapp, which are becoming increasingly important in political campaigning.